Musibah dalam Tafsir al-Azhar dan Tafsir al-Misbah - El-Karimah, Mia Fitriah (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2023)
This article describes how the Qur'an explains the calamities that befall humans. One form of disaster is natural disasters that often occur in Indonesia, so the author takes two interpretations of Indonesian scholars, namely Tafsir Al-Azhar and Tafsir Al-Misbah. This research as a whole is a library research. The author uses the maudhû`i interpretation approach (thematic) & comparative approach, the data that has been collected is analyzed using the interpretation and comparison (muqarran) method of both interpretations. The results of this study conclude that in interpreting verses related to the nature of disasters, both Hamka and M. Quraish Shihab have the same opinion, that calamities that befall humans have essentially been written in Lauhul Mahfudz and with the permission and will of Allah SWT, the difference is when the term Hamka's use of the Qur'an for the meaning of calamity is not mentioned by Hamka while M. Quraish Shihab explains the meaning and differences in scope. Hamka classifies disasters into big and small disasters, in contrast to M. Quraish Shihab, both of them have the same view that disasters occur as a result of human actions themselves, only Hamka emphasizes in his interpretation, not to blame others easily. the same view that when a disaster befalls a human being he should be patient, grateful and trustful and say the sentence istirja'.